Image properties of Malaysian rice grains during the maturing process - Choe, Lip Haw (2014)
Quality of harvested rice and its production are influenced by harvesting day.Harvesting at the right time gives the best yield and best quality. The purpose of this research was to determine image properties of paddy during maturing process, and evaluate the losses and quality of grain when harvested in different maturing period. Parameters such as weight of florets, hardness of florets, hue colour of florets, and hue colour of flag leaf were determined. The trends of the changes were observed towards maturity until 2 weeks after harvesting day. The research was carrying out at Sekinchan rice field where the samples were cultivated as usual. Destructive sampling test was carrying out for grains’ hardness test and grains’ weight test, while grains’ colour test and flag leaf colour test was non-destructive test. The rice variety that was use in the research was Malaysia Rice (MR) 220. The hue value for florets maturation is 40o, and 61o for leaf hue colour. In the period of maturity, the florets’hue value decreased from green to yellowish and remained constant at 40o. The maturity process began gradually from florets at outermost spikelet to florets at basal part. Florets at basal part matured 8 days later than the florets at apical part. Results show that the colour changes of leaf linearly decreased from green to yellowish. It was observed that the weight for a matured floret increased rapidly towards maturity,but remained constant when it reached mature stage. The mature floret can weight up to 28.8mg, and later dropped gradually due to loss of moisture contents after the optimum maturity stage. The hardness of florets may not able to deliver good correlation, as it had constraint when florets were in milky stage, the hardness of floret at optimum maturity stage was 64 N. Optimum harvesting day was 108 days after sowing (DAS). It was concluded that maturity of paddy can be observed, and losses of yield can be evaluated through colour of leaf, and colour of the florets. Harvesting at 2 days before or after the optimum harvesting day, the yield reduced by 1.5%, and after 4 days, yields reduced by 3%. Optimum harvesting day can be predicted through floret’s colour with accuracy of 93.1%, and flag leaf’s colour with accuracy of 90.3%.